Transcriptomic and Lipidomic Analysis of Lipids in Forsythia suspensa - Wu, Bei; Li, Yinping; Zhao, Wenjia; Meng, Zhiqiang; Ji, Wen; Wang, Chen (Frontiers in Genetics, 2021)
Forsythiae Fructus is widely used in traditional Chinese medicine. The lipid components in F. suspense are the material basis of plant growth and active metabolites. Samples were collected at two growth stages for a comprehensive study. Transcriptome and lipidomics were performed by using RNA-seq and UHPLE-Q-TOF-MS technique, separately. For the first time, we reported 5802 lipid components in Forsythia suspense fruit. Among these lipids isolated from Forsythiae Fructus, 139 lipids showed significant differences between the two stages. Glycerophospholipds and fatty acyls were the most different lipids. The content of 71.49% terpenoids decreased, and 60.00% flavonoids content increased. RNA-Seq analysis revealed 92294 unigenes, and 1533 of them were found differentially expressed. Analysis of the correlation between the lipidomics profiles and transcriptome profiles identified that the 9 key genes related to Terpenoid backbone biosynthesis pathway and 23 key genes related to other terpenoid-quinone biosynthesis pathways were differentially expressed. In phenylpropanoid pathway, 5 key genes were predicted. These results provide valuable reference information for further study of lipids of Forsythia suspense.